A Voltage Control Model of Multi-ports DC Transformer. Issue 1 (January 2021) - Wu, Hao
Abstract: DC transformer (DCT) is basic and important power conversion equipment in DC distribution network. DC transformer adopts power electronic switches and high-frequency transformer, which can realize power conversion. Multi-ports DCT can connect many different types of power supply or load equipment, and can flexibly control the current, voltage and power flow of multiple ports, which is widely used in DC distribution network. In this paper, the output voltage control model of multi-ports DCT in steady state is established. Combined with the control model, the mechanism of controlling the phase-shift angle to realize the output voltage control is proved mathematically. The correctness of the control model is verified by simulation.